Classical Compton scattering with high intensity twisted fields - Nieto Chaupis, Huber (2016)
We have studied the different forms of emitted radiation by a free electron when is under interaction by a superintense twisted field. The fundaments of this study are based in the mathematical development as derived in Ref [1], inside the covariant classical electrodynamics. Because the expansion of the twisted field onto integer-order Bessel functions, we have assumed various possibles scenarios of twisted fields through the forms Asinp(π/Δ)Jm (π/Δ)Jn(π/Δ), Acosr(π/Δ)Jn(π/Δ), AJm (π/Δ), and A Jp m(π/Δ)/(π/Δ)q, with m, n, p, q, r integers, Δ pulse laser parameter, Jm, n the Bessel functions, and π the covariant quantity. The resulting spectra have indicated that the twisted fields of order of eV interacting with a free electron with energies of order of 50 GeV might also be an interesting source of X-rays of order of 50 keV for laser intensities of order of 1018 W/cm2.